Coagulotoxic effects by brown snake (Pseudonaja) and taipan (Oxyuranus) venoms, and the efficacy of a new antivenom. (August 2019) - Zdenek, Christina N.; Hay, Chris; Arbuckle, Kevin; Jackson, Timothy N.W.; Bos, Mettine H.A.; op den Brouw, Bianca; Debono, Jordan; Allen, Luke; Dunstan, Nathan; Morley, Terry; Herrera, María; Gutiérrez, José M.; et al.
Abstract: Snakebite is a neglected tropical disease that disproportionately affects the poor. Antivenom is the only specific and effective treatment for snakebite, but its distribution is severely limited by several factors, including the prohibitive cost of some products. Papua New Guinea (PNG) is a snakebite hotspot but the high costs of Australian antivenoms (thousands of dollars per treatment) makes it unaffordable in PNG. A more economical taipan antivenom has recently been developed at the Instituto Clodomiro Picado (ICP) in Costa Rica for PNG and is currently undergoing clinical trials for the treatment of envenomations by coastal taipans ( Oxyuranus scutellatus ). In addition to potentially having the capacity to neutralise the effects of envenomations of non-PNG taipans, this antivenom may have the capacity to neutralise coagulotoxins in venom from closely related brown snakes ( Pseudonaja spp.) also found in PNG. Consequently, we investigated the cross-reactivity of taipan antivenom across the venoms of all Oxyuranus and Pseudonaja species. In addition, to ascertain differences in venom biochemistry that influence variation in antivenom efficacy, we tested for relative cofactor dependence. We found that the new ICP taipan antivenom exhibited high selectivity for Oxyuranus venoms and only low to moderate cross-reactivity with any Pseudonaja venoms. Consistent with this genus level distinction in antivenom efficacy were fundamental differences in the venom biochemistry. Not only were the Pseudonaja venoms significantly more procoagulant, but they were also much less dependent upon the cofactors calcium and phospholipid. There was a strong correlation between antivenom efficacy, clotting time and cofactor dependence. This study sheds light on the structure-function relationships of the procoagulant toxins within these venoms and may have important clinical implications including for the design of next-generation antivenoms. Highlights: Pseudonaja venoms were shown to be more potently procoagulant than Oxyuranus . Oxyuranus antivenom performed poorly against Pseudonaja venoms. Cofactor biochemistry was a significant variable in venom potency.